Begin at the beginning: economic analysis of the role of corporate law - Forno Odría, Hugo (2017)
Fundamental rights as private autonomy and business freedom prevent individuals from being unjustifiably restricted from doing a risk analysis and regulating their interests as they please. A restriction is only justified when transaction costs are prohibitive, which depends of the agents that intervene on the economic sector where each regulation is directed. In this article, the author seeks to determine the necessity -if any- of Corporate Law in Peru. In order to achieve this, concepts like Coase’s theorem, the principle of regulatory subsidiarity and different company’s theories will be used and developed. Also, this article seeks to present which tools does individuals possess when a corporate regulation already in force contravenes its own function.